SARANA PENDIDIKAN, KESEHATAN DAN TINGKAT KEMISKINAN DI KECAMATAN TANJUNG SEBAGAI PUSAT PERTUMBUHAN KABUPATEN LOMBOK UTARA, PASKA GEMPA 2018 DAN MASA PANDEMI COVID-19 - MUHAMMAD ALWI; PUTU KARISMAWAN; I DEWA KETUT YUDHA S; IWAN HARSONO (Universitas Mahasaraswati K. Mataram, 2022)
Earthquake 2018 and than Covid-19 Pandemic as starting point to conduct research about condition of educations, healties and rate of poverty in Tanjung Districts, North Lombok, West Nusa Tenggara Province. Base on analysis data of centre of Statistic Bureau of North Lombok (BPS) and population projection of Tanjung districts untill 2025, the condition are: fasilities of kindergarten has not been enough yet. The distibution of that finfrastructure among the vilages is not equal. The elemnteray or primary school (Sekolah Dasar), junior high school ( Sekolah Menengah Pertama) are more than enough, Midle high school (sekolah Menengah Atas) are not enough yet. The aditional education fasilities in 2022 need to add, such as 20 units of new kindergarten, 1 units of Midle high school. Health fasilities relatively has not been enough yet, compare to district Tanjung population as much 220.412 and the position distric Tanjung as capital of North Lombok regency e.g community helath centre and sub community health centre (Puskesmas dan Puskesmas Pembantu), polyclinic and laboratory, hospital, private doctor services, farmacy are not enough yet realtively to population. It should there 5 unit of Community health centre dan 82 sub cummunity helath centre, 10 private doctor services, 1 unit of laboratory, 3 unit of hospital C or 1 B type. Base on qualitative data that rate of poverty in Tanjung district is relativly high. The lowest education level, skill, Lack of employment opurtunity, and capital are the prime faktor of poverty